The people aspects in modern process improvement management approaches. Issue 4 (2nd November 2011) - Korsaa, Morten; Johansen, Jörn; Schweigert, Tomas; Vohwinkel, Detlef; Messnarz, Richard; Nevalainen, Risto; Biro, Miklos; Biró, Miklós; Messnarz, Richard; Palacios, Ricardo Colomo
<x xml:space="preserve">Abstract</x> It is well‐known that process improvement change requires "tools‐processes‐people." Engineers have spent most energy on the tools and processes, but everything is done by people, and success depends on people and their competencies. The increasing focus on people is reflected in many change models; some are discussed in this paper. <boxed-text content-type="graphic" id="smr570-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text>